ANALISIS KINERJA KEUANGAN PADA BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH (STUDI KASUS: BANK KB BUKOPIN) - Dissa Ariany (2022)
Financial performance is a description of the analysis of the existing financial condition of the company, so that it can be known whether the financial condition of a company is good or bad so that it can reflect the company's work performance in a certain period. To find out the comparison of the financial performance of conventional commercial banks and Islamic commercial banks at bank kb bukopin using the RGEC method, the method used in measuring financial performance is the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) method which replaces the previous method, namely CAMELS. . Where with the RGEC method, bank management needs to pay attention to general principles as the basis for assessing financial performance, namely: risk-oriented, proportionality, materiality, and significance, as well as comprehensive and structured. The financial data used in writing this Final Project is taken from the website of each bank. Conventional Bank KB Bukopin has better financial performance than Sharia Bukopin KB Bank. It is clearly seen that Bank KB Bukopin Conventional experienced a drastic financial decline, but in the near term Bank KB Bukopin Conventional managed to reduce losses and managed to improve financial performance even though it was still losing money, at least the losses that must be borne by Conventional Bukopin KB Bank were reduced. This conclusion shows that conventional Bank KB Bukopin has better financial performance than Sharia Bank KB Bukopin.